DIRECTIONS OF DEVELOPMENT AND IMPLEMENTATION OF THE UKRAINIAN EXPORT POTENTIAL - Rostyslav FEDIV; Iryna FEDIV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article are researched the main trends of forming and realization of the agrarian enterprises’ export potential. There is conducted an analysis of interdependance between the separate factors (in particular, investments into the agrarian sector) and the quantitative indicators of the export potential development. There are proposed the ways of the agrarian enterprises’ export potential realization within the context of the eurointegrational processes, which harbour contemporary specificities of the agrarian enterprises development, tendencies of the agrarian enterprises’ foreign economic activity and the analysis of the possible opportunities and main threats for Ukrainian enterprises when carrying out the export activity. There is produced a typical algorithm of the certification undergoing devoted to the agricultural commodities export in accordance to the European requirements under the GlobalGAP standards, that will facilitate the growth in production of the agricultural products, specially for the sale onto the European markets.